Tourists perception and satisfaction and towards local food in Muar, Johor. - Amran, Fatiha; Saad, Mazni (2020)
Food Tourism is related to tourists' behavior, knowledge of local food, food image, the evolution of food, food providers, street food and memorable experiences. Thus, tourists’ satisfaction will determine tourists’ intention to re-visit destination as well as promoting destination through words-of-mouth and review through website or social media. However, Malaysia local foods still are insufficient considerations about the tourists’ food experiences especially in terms of satisfaction. Therefore, this paper aims to determine tourists’ perception and satisfaction on local foods, to investigate the local foods as potential to enhance tourists’ experienced and to explore the factors on tourists’ perception and satisfactions based on their local food experience in Muar. Hence, it is crucial for the destination management to constantly make an effort to improve and enhance dining experience for the destinations. The study was carried out by conducting interview 6 respondents who is going to Muar for specifically food hunting and analyses the data using Microsoft Words transcribe and using thematic analysis to arranging the data according to themes.